CO27 | Intracerebral hemorrhage in hemophilia A and B: a 10-year prospective multicenter study in Italy (2012–2022) (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Intracerebral hemorrhage (ICH) is a severe and life-threatening complication in patients with hemophilia, often resulting in high mortality and long-term neurological impairment. Despite its clinical importance, prospective data on ICH incidence, associated risk factors, and outcomes in hemophilia A and B remain scarce. This study aimed to evaluate the prevalence, clinical features, risk factors, and long-term outcomes of ICH in a cohort of patients with hemophilia A and B over a 10-year period.